Identification of a Novel Defined Immune-Autophagy-Related Gene Signature Associated With Clinical and Prognostic Features of Kidney Renal Clear Cell Carcinoma - Zhang, Guangyuan; Zhang, Lei; Sun, Si; Chen, Ming (Frontiers in Molecular Biosciences, 2021)
Background: As a common cancer of the urinary system in adults, renal clear cell carcinoma was metastatic in 30% of patients and died in 60% of patients 1~2 years after diagnosis. At present, the rapid development of tumor immunology and autophagy had brought new directions to the treatment of renal cancer. Therefore, it was extremely urgent to find potential targets and prognostic biomarkers for immunotherapy combined with autophagy. Methods: Through GSE168845, immune-related genes and autophagy-related genes, immune-autophagy-related differential expressed genes (IAR-DEGs) were identified. Independent prognostic value of IAR-DEGs was determined by differential expression analysis, prognostic analysis, univariate and multivariate Cox regression analysis. Then, the lasso Cox regression model was established to evaluate the correlation of IAR-DEGs with immune score, immune checkpoint, iron death, methylation, and OCLR score. Results: In this study, it was found that CANX, BID, NAMPT and BIRC5 were immune-autophagy related genes with independent prognostic value, and the risk prognostic model based on them was well constructed. Further analysis showed that CANX, BID, NAMPT, BIRC5 were significantly correlated with immune score, immune checkpoint, iron death, methylation, and OCLR score. Further experimental results were consistent with the bioinformatics analysis. Conclusions: CANX, BID, NAMPT and BIRC5 were potential targets and effective prognostic biomarkers for immunotherapy combined with autophagy in kidney renal clear cell carcinoma.